Share Price Analysis for Selected Companies based on Human Resource Practices - Roux, Corlise Liesl Le (Ushus Journal of Business Management, 2021)
This paper investigates the links between human resources, finance and investments. These departments should work towards the same goal of producing profitability for the organisation and a high level performance. Without this, the organisation does not benefit from the skills in both teams. To highlight the link, finance and investment related measures linked to the price of 12 top ranking and 12 bottom ranking companies from the 2017 Workforce 100 list are evaluated to determine if differences exist in their share price performance. The selected companies are evaluated against selected benchmarks, NASDAQ Composite index as well as the NYSE Composite Index, to analyse their financial performance on a very high level. The analysis includes visual display of the logged share prices of the selected companies included in the study followed by year percentage change comparison and P/E ratio comparison to determine any fundamental differences. The top 12 ranking listed companies showed a higher year percentage change in 2017 based on share prices as well as a higher P/E ratio.